The concepts of early Urdu fiction writers - Sanobar Altaf (بازیافت)
In the days when novel was appearing in Urdu due to European influences, literature was inspired by social and developmental concepts in Europe. In sub-continent, however, modern movements under the influence of British colonialism were dominated by socio-political aspects. Inevitably, its influence on the early Urdu fiction writers was profound. In this regard, the purpose of the Sir Syed's movement, its literary and social aspects and their influence was very prominent. It was acting as the first wave of modernity among Indian Muslims. Maulvi Nazir Ahmad, the first Urdu novelist considered an important part of “Arkaan e khumsa”. His ideas about the novel are reflected in the preface that was part of his early publications. Similarly, other early Urdu novelist like Abdul Haleem Sharer, Ratan Nath Sarshar, Mirza Hadi  Ruswa and Premchand have explained the concept and purpose of the novel in their articles. This article takes account of these concepts in light of their fictional works.